Integrated Marketing Communication dalam Mempromosikan Wisata Waduk Gajah Mungkur di Era Digital - Syafa Aziz Syaputra; Hasbullah Azis; Rahmat Wisudawanto (Institut Nalanda, 2024)
Tourism plays a crucial role as a key driver of economic growth and national development, making the planning and promotion of this sector essential. This study aims to analyze the Integrated Marketing Communication (IMC) strategies implemented by DISPORA in promoting tourism at the Gajah Mungkur Reservoir in the digital era. A qualitative approach was employed to illustrate the IMC strategies used to attract visitors. The findings of the study indicate that DISPORA's IMC strategy has been successful in building a strong brand image and attracting tourists through word-of-mouth marketing, social media platforms (Instagram and Facebook), and consistent messaging across channels. Notably, the use of social media as the primary platform has proven effective in capturing visitor interest through engaging visual content. However, the study also identifies weaknesses in sales promotion efforts, such as the lack of discounts and loyalty programs. To enhance the effectiveness of their campaign, it is recommended that DISPORA improve the quality of digital content, provide staff training on digital technology and social media, and collaborate with influencers to expand promotional reach.